Enhancing Māori and Pasifika graduate interest in ophthalmology surgical training in New Zealand/Aotearoa: Barriers and opportunities. (19th May 2020) - Freundlich, Simone E. N.; Connell, Charlotte J. W.; McGhee, Charles N. J.; Cunningham, William J.; Bedggood, Antony; Poole, Phillippa
Abstract: Importance: Improving the representation of indigenous ophthalmologists in New Zealand. Background: Māori, indigenous to New Zealand/Aotearoa and Pacific Peoples indigenous to Pacific Island Nations living in New Zealand, experience poorer health outcomes across several ophthalmic conditions. The Royal Australian and New Zealand College of Ophthalmologists have identified indigenous workforce development as a priority. Design: Mixed‐methods study, utilizing retrospective analysis of Medical Schools Outcomes Database and Longitudinal Tracking Project responses, and prospective interviews with Māori/Pasifika medical graduates. Participants: This study involved 64 medical graduates from the University of Auckland (UoA) and the University of Otago, and six Māori/Pasifika medical postgraduates in New Zealand. Methods: Retrospective analysis of medical graduate responses who ranked ophthalmology among their top‐three preferred specialties in the Medical Schools Outcomes Database and Longitudinal Tracking Project. Prospective semi‐structured interviews with Māori/Pasifika medical postgraduates. Main Outcome Measures: Specialty training influencing factors and prevocational ophthalmology experience. Results: A total of 64 (6.7%) out of 954 medical graduates from the UoA and University of Otago ranked ophthalmology among their top‐three preferred training specialties (2012‐2017). Of the 64 graduates, six (9.3%) identified as Māori/Pasifika. No significant difference in influencing factors between Māori/Pasifika and non‐Māori/Pasifika students was identified. Both groups ranked intellectual content, procedural skills, specialty exposure and mentorship as highly influential. Qualitative interviews with Māori/Pasifika graduates highlighted positive experiences in ophthalmology but limited exposure overall. Negative anecdotes and unclear training pathways discouraged Māori/Pasifika interest in Ophthalmology training. Conclusions and Relevance: Māori/Pasifika graduate interest in ophthalmology training was relatively low. Valuable insights include enhancing specialty exposure, mentor development, promoting Māori/Pasifika connections and clarifying training pathways for future graduates.